The “forgotten” treatment of alcohol withdrawal delirium with electroconvulsive therapy: successful use in a very prolonged and severe case - Kranaster, Laura; Janke, Christoph (Clinical neuropharmacology, 2017)
Objective Alcohol withdrawal delirium (AWD) is a notorious complication in alcohol withdrawal. Usually, the symptomatic treatment is efficacious; however, some patients show treatment resistance or a prolonged course of AWD. Method We report the case of a patient with a prolonged and severest form of AWD. Even 11 weeks after admission, he received approximately 100 mg diazepam per week to manage the symptoms of withdrawal delirium. Results A treatment course of electroconvulsive therapy was initiated, which allowed a complete tapering off of benzodiazepines during electroconvulsive therapy without adverse effects. Conclusions The reported case might contribute to alternative approaches reserved for severest forms of prolonged AWD.